Analisis Keterampilan Berbicara Siswa Kelas III MI Nurul Hikmah dalam Pembelajaran Tematik - Nurvia Urfany; Dilla Fadhillah; Eka Kurniawan Yulyawan (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2024)
This study aims to describe how the speaking skills of third grade students of MI Nurul Hikmah in thematic learning. Speaking is a very important skill in everyday life, indirectly speaking activities will hone one's communication skills. Speaking skills become something that is very influential on the school or educational environment, family and other public environments. It is very important for everyone to develop their speaking skills. This research uses a qualitative approach with the subject of Teachers and Students. In collecting data, researchers used observation methods, interviews, oral tests and documentation studies. The results of this study speaking skills on the subject of research students grade III MI Nurul Hikmah seen in the indicators used consist of pronunciation, intonation, vocabulary or sentences, memorization, and mimic or expression. From several indicators of speaking skills, it shows that there is only 1 student who obtained a very good category, 3 students obtained a good category, as many as 9 students obtained a sufficient category, 3 students obtained a less category, and 3 students obtained a very poor category. With the results of the tests conducted, the level of speaking skills of grade III MI Nurul Hikmah in thematic learning is in the good enough category.